Characterization of brown adipose tissue by water–fat separated magnetic resonance imaging. Issue 6 (25th April 2015) - Romu, Thobias; Elander, Louise; Leinhard, Olof Dahlqvist; Lidell, Martin E; Betz, Matthias J; Persson, Anders; Enerbäck, Sven; Borga, Magnus
Abstract : Background: To evaluate the possibility of quantifying brown adipose tissue (BAT) volume and fat concentration with a high resolution, long echo time, dual‐echo Dixon imaging protocol. Methods: A 0.42 mm isotropic resolution water–fat separated MRI protocol was implemented by using the second opposite‐phase echo and third in‐phase echo. Fat images were calibrated with regard to the intensity of nearby white adipose tissue (WAT) to form relative fat content (RFC) images. To evaluate the ability to measure BAT volume and RFC contrast dynamics, rats were divided into two groups that were kept at 4° or 22°C for 5 days. The rats were then scanned in a 70 cm bore 3.0 Tesla MRI scanner and a human dual energy CT. Interscapular, paraaortal, and perirenal BAT (i/pa/pr‐BAT) depots as well as WAT and muscle were segmented in the MRI and CT images. Biopsies were collected from the identified BAT depots. Results: The biopsies confirmed that the three depots identified with the RFC images consisted of BAT. There was a significant linear correlation ( P  < 0.001) between the measured RFC and the Hounsfield units from DECT. Significantly lower iBAT RFC ( P  = 0.0064) and significantly larger iBAT and prBAT volumes ( P  = 0.0017) were observed in the cold stimulated rats. Conclusion: The calibrated Dixon images with RFC scaling can depict BAT and be used to measure differences in volume, and fat concentration, induced by cold stimulation. The high correlation between RFC and HU suggests that the fat concentration is the main RFC image contrast mechanism. J. MAGN. RESON. IMAGING 2015;42:1639–1645.